Appropriate Use of Proton Pump Inhibitors in General Out Patient Department of a Tertiary Care Center of Kathmandu Valley: An Observational Study - Jeetendra Bhandari; Narendra Bhandari (Journal of Nepal Medical Association)
Introduction: Proton Pump Inhibitors (PPIs) are widely used medications that suppress gastric acid secretion worldwide. However, they have been linked to an increased risk of chronic kidney disease, hypomagnesemia, and bacterial infections, including C. difficile and acid hypersecretion. This study aimed to identify the appropriateness of PPI prescriptions in general clinics. Methods: An observational cross-section study was conducted in General out patient department of a tertiary care center of Nepal . Purposive sampling was done. The study included 355 clinical notes from the clinic’s out patient department with at least one proton pumb inhibitor prescription. Data was collected, and the proportion of different parameters was calculated. Results: Appropriate use of proton pumb inhibitor was 255 (57.74%). Among the total study population, 186 (51.22%) were male. The appropriate use of proton pump inhibitor use by faculties was 83 (61.02%) and 68 (33.68%) reported that it was given to prevent Non-steroidal Anti-Inflammatory Drug-related complications. Pantoprazol was prescribed in 256 (74.62%) cases. Conclusions: This study suggests that PPIs were appropriate more than 50 percent of the time, but a high number of patients have been prescribed PPIs without a clear indication.